Needs And Approaches For In-Service Teacher Training At Elementary Level - Patel, Kalyani (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The purpose of education is to bring out changesin behaviour of the children and shape their personality in a desirable and acceptable manner. Teaching is one of the best demanding profession in the world and Teacher is the most important person to handle the teaching-learning situation. It is essential for the teachers to play their role with excellence for achieving desirable learning outcomes. Hence, their capacity building is felt necessary.